Analysis of delivery pattern and neonatal outcome in the calendar year 2015 in urban field practice area of Kamineni Institute of Medical Sciences, Narketpally, India - Balmur, Sarala K.; Guthi, Visweswara R.; Naidu, Navya K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Neonatal mortality is the number of neonatal deaths in a given year per 1000 live births in that year. It is estimated that 5.9 million children under 5 years of age died in 2015, with a global under-five mortality rate of 42.5 per 1000 live births. Of those deaths, 45% were newborns, with a neonatal mortality rate of 19 per 1000 live births. The present study aimed at to assess the neonatal mortality in the study area and to study the socio demographic factors, obstetric and neonatal factors among study population. Methods: This is a Cross-sectional study conducted in the field practice area of Urban Health Centre (UHC) under department of Community Medicine, KIMS, Narketpally, Nalgonda district, Telangana from February 2016 to April 2016. A total of 240 women were included in the study. Information collected was their socio-demographic data, previous and present obstetric history and utilization of health facilities and condition of Baby after birth. Results: Neonatal mortality rate in the study area during the study period is 8.39/1000 live births. Out of 242 new born babies 129(53.3%) were males and 113 (46.7%) were females. Majority (94.2%) had a birth weight of more than 2.5 kgs. Out of 242 babies 7 babies were suffering from congenital anomalies (2), Sepsis (2) and skin infections (3). Conclusions: Most of the study population were in the age group of 19-25 years, literates, laborers by occupation, Hindu by religion, belong to nuclear families and belong to below poverty line. Most of the new born babies have birth weight >2.5 kgs.